EKSISTENSI INDUSTRI PIS BOLONG SEBAGAI MEDIA SOSIALISASI RELIGIUSITAS BUDAYA BALI BAGI WISATAWAN DI DESA KAMASAN, KLUNGKUNG - Putu Sabda Jayendra (STIE BIITM, 2019)
Tourism in Bali is dominated by cultural tourism inspired by the religiosity of Hinduism. The potential of Balinese religion and culture gives birth to many cultural products that become excellent tourist destinations. In this case, Kamasan Village, located in Klungkung Subdistrict, Klungkung Regency, has one of the mainstay products in the form of pis bolong (Uang Kepeng). The perforated industry in the village of Kamasan in this case is not only a tourist attraction, but also as a medium to socialize the religiosity of Balinese culture for tourists. In this case, tourists not only enjoy the destination, but also learn about religious and magical Balinese culture. This is very important to be studied in the midst of the massive phenomena of the degradation of the Balinese people's understanding of cultural religiosity, one of which is caused by the widespread circulation of imitation pis which is not in accordance with the religious principles of Balinese culture.